Papillary renal cell carcinoma with extensive spindle cell foci: mimicker of mucinous tubular and spindle cell carcinoma - Fareed Rajack; Shawn Medford; Tammey Naab (University of São Paulo, 2024)
Papillary renal cell carcinoma (PRCC) is the second most common renal cell carcinoma (RCC), accounting for 10-15% of cases. Mucinous tubular and spindle cell carcinoma (MTSCC), on the other hand, accounts for only 1% of renal tumors and has a more favorable prognosis compared to PRCC. We report a 75-year-old female with a left upper pole solid renal mass displaying features of both papillary renal cell carcinoma (PRCC) and mucinous tubular and spindle cell carcinoma (MTSC). In this case, a shaggy luminal surface, multiple papillations, and psammoma bodies, absence of E-cadherin expression, and strong CD10 expression favored PRCC. Both immunohistochemistry and genomic analysis are critical to diagnose and differentiate tumors that may have overlapping features accurately.